2015
DOI: 10.1002/ase.1527
|View full text |Cite
|
Sign up to set email alerts
|

Using guided inquiry and the information search process to develop research confidence among first year anatomy students

Abstract: With the growing volume of obtainable medical information and scientific literature, it is crucial that students in the field of allied health professions develop and refine the research skill set necessary to effectively find, retrieve, analyze, and use this information. This skill set can be effectively developed using student inquiry; an active learning process where students answer questions using research and data analysis. Therefore, with the pedagogical goal of developing information literacy among a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The results of the study displayed that the students developed their critical thinking, scientific process skills and reacted positively to the application. Bentley, Robinson and Ruscitti (2015) showed that following to the inquiry guided learning projects, the students who participated in the study developed their self confidence and some of the research skills. Additionally, Wang, Núñez, Maxwell, and Algar (2016) designed a guided-inquiry project to teach spectrophotometric instrumentation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study displayed that the students developed their critical thinking, scientific process skills and reacted positively to the application. Bentley, Robinson and Ruscitti (2015) showed that following to the inquiry guided learning projects, the students who participated in the study developed their self confidence and some of the research skills. Additionally, Wang, Núñez, Maxwell, and Algar (2016) designed a guided-inquiry project to teach spectrophotometric instrumentation.…”
Section: Resultsmentioning
confidence: 99%
“…Both inquiry‐based and authentic approaches to learning encourage drawing on students' own daily lives to contextualize learning and make it more meaningful. Inquiry‐based learning has been used in a variety of anatomy classroom contexts to foster research skills and confidence (Bentley et al, ; Chaplin, ), deepen understandings of course content (Chaplin, ; Lee et al, ), and encourage higher levels of engagement and interest in disciplinary practice (Meuler, ). Similarly, authentic learning, in the context of anatomy education, has been identified as a possible approach for teaching students to meaningfully interpret anatomical practices, problem solving, and application (Lombardi, ; Pawlina and Drake, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inquiry‐based learning involves students' active and increasingly independent investigation of questions and problems that are of interest to them through process of scientific inquiry (Dewey, ; Lee et al, ). Studies of students' IBL engagement within anatomy classrooms have shown statistically significant gains in learners' self‐perceived research confidence and abilities (Bentley et al, ; Chaplin, ) as well as improved understandings of the content learned (Chaplin, ). Studies have also found IBL to facilitate deep learning (Lee et al, ), improve examination performance (Brown, ), strengthen learner satisfaction (Hermiz et al, ), and encourage higher levels of engagement and interest in the discipline (Meuler, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anstey () reported that inquiry learning in anatomy, where students pursue their own interests, provided an unique learning experience for students driven by their own curiosities. Furthermore, studies of IBL in anatomy classrooms have shown gains in self‐perceived research abilities (Bentley et al, ) and an improved understanding of content learned (Chaplin, ). In this way inquiry‐based learning is an effective tool in reinforcing anatomical content knowledge but also in developing the transferable skills that are required of graduates in professional settings.…”
Section: Discussionmentioning
confidence: 99%